An enhanced regimen as post-exposure chemoprophylaxis for leprosy: PEP - Mieras, Liesbeth F; Taal, Anna T; van Brakel, Wim H; Cambau, Emmanuelle; Saunderson, Paul R; Smith, W Cairns S; Prakoeswa, Cita Rosita S; Astari, Linda; Scollard, David M; do Nascimento, Dejair Caitano; Grosset, Jacques; Kar, Hemanta K; et al. (BMC infectious diseases, 2018)
The ongoing transmission of Mycobacterium (M.) leprae reflected in a very slow decline in leprosy incidence, forces us to be innovative and conduct cutting-edge research. Single dose rifampicin (SDR) as post-exposure prophylaxis (PEP) for contacts of leprosy patients, reduces their risk to develop leprosy by 60%. This is a promising new preventive measure that can be integrated into routine leprosy control programmes, as is being demonstrated in the Leprosy Post-Exposure Programme that is currently ongoing in eight countries. The limited (60%) effectiveness of SDR is likely due to the fact that some contacts have a preclinical infection beyond the early stages for which SDR is not sufficient to prevent the development of clinical signs and symptoms of leprosy. An enhanced regimen, more potent against a higher load of leprosy bacteria, would increase the effectiveness of this preventive measure significantly. The Netherlands Leprosy Relief (NLR) is developing a multi-country study aiming to show that breaking the chain of transmission of M. leprae is possible, evidenced by a dramatic reduction in incidence. In this study the assessment of the effectiveness of an enhanced prophylactic regimen for leprosy is an important component. To define the so called PEP++ regimen for this intervention study, NLR convened an Expert Meeting that was attended by clinical leprologists, public health experts, pharmacologists, dermatologists and microbiologists. The Expert Meeting advised on combinations of available drugs, with known efficacy against leprosy, as well as on the duration of the intake, aiming at a risk reduction of 80–90%. To come to a conclusion the Expert Meeting considered the bactericidal, sterilising and bacteriostatic activity of the potential drugs. The criteria used to determine an optimal enhanced regimen were: effectiveness, safety, acceptability, availability, affordability, feasibility and not inducing drug resistance. The Expert Meeting concluded that the enhanced regimen for the PEP++ study should comprise three standard doses of rifampicin 600 mg (weight adjusted when given to children) plus moxifloxacin 400 mg given at four-weekly intervals. For children and for adults with contraindications for moxifloxacin, moxifloxacin should be replaced by clarithromycin 300 mg (weight adjusted).